Peningkatan Semangat Kerja Pegawai Melalui Motivasi Kerja, Lingkungan Kerja dan Komunikasi - Renny mointi; Ferdinan Poylema; Oktovianus Sauw; Syahrul Makkuradde (Jurnal Mirai Management, 2021)
The purpose of this study was to analyze the effect of work motivation, work environment and communication on employee morale. This research approach uses a scientific approach to test the justification of the proposed hypothesis with statistics until it finds. The population in this study were 60 administrative employees of PT PLN (Persero) Parent Unit for South Sulawesi Region. The sampling technique uses a saturated sample technique. Collecting data in this study is by distributing questionnaires directly to the administrative staff of PT PLN (Persero) Parent Unit for Sulselrabar Region. Then to test the relationship between variables, this study conducted multiple regression analysis through the SPSS program. The results of this study found that there was a positive and significant influence on work motivation, work environment and communication on employee morale. The results of this study are expected to strengthen existing empirical evidence and can contribute input in building employee morale at PT PLN (Persero) Main Unit for South Sulawesi Region. Keywords: Work Motivation, Work Environment ,Communication, Employee Morale.